Association of Arterial Stiffness With Obesity in Australian Women: A Pilot Study. Issue 2 (28th November 2012) - Pal, Sebely; Radavelli‐Bagatini, Simone
<x xml:space="preserve">Abstract</x> This study investigated the arterial stiffness status in overweight/obese Australian women compared with their lean counterparts. Twenty‐six Caucasian women were designated into one of two groups: overweight/obese (body mass index [BMI] 25–34.9 kg/m2[ n=12]) and lean (BMI 18.5–24.9 kg/m2 [n=14]) groups. Participants were assessed for clinical, anthropometric, metabolic, and augmentation index (AIx) measurements. Age was similar between groups (P=.482). BMI was significantly higher in overweight/obese compared with lean participants (30.26±1.09 vs 21.62±0.52 kg/m2, P=.001) as well as the percentage of body fat (40.60±2.43 vs 21.57±1.13, P=.001), waist circumference (91.47±2.77 vs 70.67±1.60, P=.001), and waist/hip ratio (0.81±0.04 vs 0.71±0.03, P=.036). Overweight/obese group showed higher total cholesterol, triglyceride, low‐density lipoprotein cholesterol, and fasting glucose levels compared with the lean group (all P<.05). Both systolic (122.92±3.18 mm Hg vs 108.14±2.42 mm Hg, P=.001) and diastolic (83.58±2.43 mm Hg vs 72.43±1.29 mm Hg, P=.0001) blood pressures, as well as AIx (50.08±4.7 vs 120.79±2.17, P=.001) were significantly higher in the overweight/obese group compared with the lean group. AIx was positively associated with measurements of body composition (P<.05), triglycerides (r=0.361, P=.035) and glucose levels (r=0.371, P=.031), and systolic and diastolic blood pressure (r=0.793 and r=0.718, respectively; P=.0001). This data suggests that arterial stiffness is associated with obesity, along with other metabolic abnormalities in Australian women. J Clin Hypertens (Greenwich). 2012;00:00–00.©2012 Wiley Periodicals, Inc.